Isolation of Candida spp from vaginal microbiota of healthy canine females during estrous cycle - Marlete Brum Cleff; Alzira Pacheco de Lima; Renata Osório de Faria; Ana Raquel Mano Meinerz; Tatiana de Ávila Antunes; Flávia Biasoli de Araújo; Patrícia da Silva Nascente; Márcia de Oliveira Nobre; Mário Carlos Araújo Meireles (2005)
Yeasts are commensal organisms found in the skin, genital and gastrointestinal tracts, and other mucosa in mammalians. Candida spp has been frequently isolated from domestic and sylvan animals. Yeast isolation from vaginal mucus is frequent in women, especially of Candida genus. In canine females, however, studies about vaginal fungal microbiota are rare and the connection with estrous cycle is unknown. The purpose of this study was to isolate yeast 5 of Candida genus from healthy canine females and identify the isolated species, establishing their connection with estrous cycle phases. Two hundred twenty-four samples taken from vaginal mucus of 14 canine females were analyzed in this study. Candida spp was observed in 83 (37%) from these samples; nine samples were taken in proestrus, 14 in oestrus, 31 in dioestrus, 24 in anoestrus and five samples were obtained during pregnancy. Candida parapsilosis the most frequently isolated specie (21.7%), followed by C. guillermondii (8.4%), C. kefir (6%) and C. albicans (4.8%). We concluded that Candida spp is a commion component of healthy canine females' vaginal microbiota, and isolation varies according to the estrous cycle phase.